EFFECT OF MICROTUBE REACTOR INTERNAL DIAMETER ON BIODIESEL PRODUCTION FROM PALM OIL - MOHD AZAM, NURUL ASYIKIN (2017)
Biodiesel, a renewable fuel derived from vegetable oils and animal fats. Batch reactor was commonly used for fundamental study and industry. Recently several papers reported that transesterification by using micro or milli-tube reactor as a fundamental study. Generally, microtube reactor had a higher reaction rate in comparison with batch reactor at similar reaction condition. However, this research field had not been investigated thoroughly in terms of tube internal diameter effect from micrometre to millimetre. This research focused on the effect of internal diameter of micro and milli-tube reactor and factors influencing the biodiesel production which included methanol to oil molar ratio, temperature, catalyst concentration, and residence time. In addition, the geometry of microtube reactor and the comparison between batch and microtube reactor were also investigated in this research.